Empirical Path Loss Distribution for Visible Light Communications in Underground Mines - Soto-Gomez, J; Seguel-Gonzalez, F (Institute of Electrical and Electronics Engineers Inc., 2020)
Visible light communication (VLC) systems allow communication and lighting simultaneously. This advantage presents VLC as an emerging technology to provide reliable communication in harsh environments, such as underground mines (UM). To properly implement UM-VLC systems, it is imperative to study the signal propagation phenomenon, to analyze possible problems with the optical signal. Therefore, in this paper, we present the empirical path loss distribution in UM environments. Considering UM dimensions and optical signal components, path loss expressions are mathematically determined by using a curve fitting technique. Graphical and numerical results demonstrate the linear behavior of the mining path loss distributions. © 2020 IEEE.